Effect of CO2 dilution on the structure and emissions from turbulent, non-premixed methane–air jet flames. Issue 2 (April 2017) - Erete, James I.; Hughes, Kevin J.; Ma, Lin; Fairweather, Michael; Pourkashanian, Mohamed; Williams, Alan
Abstract: This investigation gives a comparison of the variation of temperature and gas compositions in lifted, turbulent non-premixed methane–air jet flames firing vertically into still air with different carbon dioxide diluent concentrations in the fuel jet. The carbon dioxide mole fraction ranged from 0 to 0.22 and was varied with a fixed jet velocity so that dilution-induced extinction was achieved. The effect of the changes due to this dilution on the post-flame emissions was investigated. Similarly, visual observation of the changes in the flame structure in mixture fraction space at different diluent mole fraction has been studied. An examination of the changes in the flame length, lift-off height, flame temperature, composition, and on the emission indices of the species in the post-flame region were made. They showed an increase in the flame's lift-off height, a decrease in the overall flame length, a reduction in the flame temperature and a reduction in the NOx concentration at various levels of dilution of carbon dioxide in the fuel. Highlights: CO2 dilution of the fuel stream in a non-premixed methane jet flame was studied. CO2 dilution leads to a decrease in the emission of NOx . CO2 dilution leads to an increase in the emission of CO. Mixture fraction plots are given of the flame structure at different diluent levels.